Investigation of possible synergistic effect of using formic acid and plant essential oil in broiler chicks drinking water on performance and gut microflora - Reza Taherkhani; Omid Parvizi; Mehran Aboozari (Network Biology, 2020)
The possible synergistic effect of using a combination of formic acid (FA) and plant essential oils (EO) in broiler chick's drinking water was investigated. Performance and gut microflora were assessed from day old to 42 d of age. The experiment was carried out using a completely randomized design with factorial arrangement (2×3). Factors were included formic acid (0, 1000 and 2000 ppm) and EO (0 and 250 ppm) level which were administered through drinking water. Both FA and EO improved performance criteria but their combination failed to create a synergistic effects. Chicks received FA supplemented water had significantly lower numbers of C. perfringens and coliforms. Administration of EO also significantly lowered numbers of gut pathogenic bacteria (C. perfringens and coliforms) while did not affect lactobacilli population. Results obtained in our study suggest a synergistic effect of using FA and EO simultaneously only in reducing gut pathogenic bacteria.